Dampak Vaksinasi Covid-19 Terhadap Saham PT Kimia Farma Tbk - Zainuri Zainuri; Nila Diansari (The Indonesia Capital Market Institute, 2022)
The first Covid-19 vaccine in Indonesia was carried out on January 13, 2021, by the President of Indonesia. This study aims to determine whether there is a significant difference in stock prices and stock trading volume due to the COVID-19 vaccination event at PT Kimia Farma Tbk (KAEF). The research data were taken 72 days before and 72 days after the vaccine event by the President of Indonesia. The data was processed using the Wilcoxon Signed Rank Test, SPSS version 25. The test results showed no significant difference in stock prices before and after vaccination by the President of Indonesia. There is a significant difference in stock trading volume on stock prices before and after vaccination by the President of Indonesia. In terms of fundamental valuation, the phenomenon of booming pharmaceutical stocks is, on average, overvalued (higher than the original price). Information regarding the vaccination event by the President of Indonesia did not make investors buy in the stock market. The euphoria of the covid-19 vaccination makes investor sentiment towards the prices of pharmaceutical stocks, especially KAEF stocks, only temporary.